Gut microbiota and body composition in anorexia nervosa inpatients in comparison to athletes, overweight, obese, and normal weight controls. Issue 12 (13th November 2017) - Mörkl, Sabrina; Lackner, Sonja; Müller, Wolfram; Gorkiewicz, Gregor; Kashofer, Karl; Oberascher, Andreas; Painold, Annamaria; Holl, Anna; Holzer, Peter; Meinitzer, Andreas; Mangge, Harald; Holasek, Sandra
Abstract: Objectives: Anorexia nervosa (AN) is a heterogeneous eating disorder associated with alterations of body structure and the gut microbiome. We aimed to investigate the gut microbiota composition of a large female cohort including different BMI groups and activity levels along with body composition parameters. Method: 106 female participants were included in this cross‐sectional study: AN patients ( n = 18), athletes ( n = 20), normal weight ( n = 26), overweight ( n = 22), and obese women ( n = 20). DNA was extracted from stool samples and subjected to 16S rRNA gene analysis. The software Quantitative Insights Into Microbial Ecology (QIIME) was used to analyze data. Additionally, we performed anthropometric assessments, ultrasound measurements of subcutaneous adipose tissue thickness, bioimpedance analysis, administered depression inventories, and ascertained laboratory parameters and dietary intakes. Results: Alpha diversity was particularly lower in AN patients and obese participants compared to other groups, while athletes showed highest alpha diversity. Several categories significantly associated with community structure were identified: body fat parameters, serum lipids, CRP, depression scales and smoking. Comparative analysis revealed Coriobacteriaceae as the only enriched phylotype in AN compared to other entities (LDA score >3.5). Discussion: This study provides further evidence of intestinal dysbiosis in AN and sheds light on characteristics of the gut microbiome in different BMI and physical activity groups. These insights point to new modulation possibilities of the gut microbiota which could improve the standard therapy of AN.